Pengembangan EDUPANK dengan Pendekatan Demonstration Setting Virtual bagi Kelompok Petambak Ikan dalam Upaya Meningkatkan Daya Tahan Tubuh di Era Pandemi Covid-19 - Atikah Rahayu; Fahrini Yulidasari; Muhammad Irwan Setiawan (Jurnal Abdimas Kesehatan (JAK), 2022)
Banjar Regency is a center for fish cultivation but the amount of fish production is not directly proportional to the people's intake of consuming fish as a source of animal protein. Imbalance between intake needs and or adequacy will cause nutritional problems such as stunting. The role and knowledge of the father is very important in influencing the growth and development of his child, considering the father as the head of the family who is responsible for his family members including avoiding stunting. Children with stunting conditions, will later become adults with low quality. If this condition occurs in children aged 0-2 years, it is very likely that the child will not be able to reach the expected potential height, the child will experience imperfect brain development, so that it has an impact on difficulties in meeting academic grades. Parental knowledge affects the occurrence of stunting in children under two. This service aims to increase the knowledge of fathers who have young children with a livelihood as farmers with the edupank program (education on the use of local food) with a demonstration approach that is carried out virtually considering the conditions of the covid-19 pandemic. All fish farmers with stunting children identified in the Banjar district were then asked for their willingness to be given education. The results of the service showed an increase in the knowledge of fish farmers before and after being given education. This percentage increase from 86% to 98% and the Wilcoxon test results show that there is a difference in knowledge before and after education (p<0.05), this means that there is an increase in the knowledge of farmers after being given education. With the modification of an attractive and well-targeted program, it is hoped that it can contribute to reducing the incidence of stunting in baduta in the Banjar Regency area.